Microstructure and tribological behavior of W-Mo alloy coating on powder metallurgy gears based on double glow plasma surface alloying technology - Wei D.-B.; Liang H.-X.; Li S.-Q.; Li F.-K.; Ding F.; Wang S.-Y.; Liu Z.-L.; Zhang P.-Z. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the present paper, plasma surface alloying was implemented on powder metallurgy gears to improve its wear resistance based on double glow plasma surface metallurgy technology. A W-Mo alloy coating was obtained in the process. The morphology, microstructure and phase composition were investigated by SEM, EDS and XRD. The hardness was examined by Vickers hardness test and nanoindentation test. The tribological behavior of powder metallurgy gears before and after plasma surface alloying was evaluated on a ball-on-disc reciprocating sliding tribometer under dry sliding condition at room temperature. The results indicate that the W-Mo alloy coating is homogeneous without defects, which includes deposition layer and interdiffusion layer. The average microhardness of powder metallurgy gears before and after plasma surface alloying is 145.8 HV0.1 and 344.4 HV0.1, respectively; Nano hardness of deposition layer and interdiffusion layer is 5.76 GPa, 14.35 GPa, respectively. The specific wear rate of W-Mo alloy coating is lower than original PM gears. The wear mechanism of W-Mo alloy coating is slight adhesive wear. The W-Mo alloy coating prepared by double glow plasma surface alloying technology can effectively improve wear resistance of powder metallurgy gears.